Tailoring P2/P3‐Intergrowth in Manganese‐Based Layered Transition Metal Oxide Positive Electrodes via Sodium Content for Na‐Ion Batteries - Kincaid Graff; Dr. Dewen Hou; Dr. Eric Gabriel; Dr. Jehee Park; Alex Koisch; Riley Schrock; Angel Conrado; Dr. Darin Schwartz; Dr. Arturo Gutierrez; Dr. Christopher S. Johnson; Dr. Eungje Lee; Prof. Dr. Hui Xiong (ChemElectroChem)
Abstract High‐manganese content sodium‐ion positive electrodes have received heightened interest as an alternative to contemporary Li‐ion chemistries due to their high abundance, low toxicity, and even geographical distribution. However, these materials typically suffer from poor capacity, unstable cycling performance, and sluggish Na+ kinetics. Herein, we explore a manganese‐based layered transition metal oxide (NaxN0.25Mn0.75O2) and show by X‐ray diffraction (XRD) and high‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM) that careful variation of the sodium content can instigate the formation of a biphasic intergrowth. This intergrown P2/P3 material offered a higher capacity than its monophasic P2 counterpart due to the P3 structure having greater low‐voltage Mn3+/4+ redox. Further, the intergrowth material offers greatly enhanced kinetics and cycling stability when compared to single‐phase P3 material, due to the stabilizing nature of the P2 structure, elucidated by galvanostatic intermittent titration technique (GITT) and operando synchrotron X‐ray diffraction. These results highlight the beneficial effect that the intergrowth structure has on the electrochemical performance of high‐manganese content positive electrode for future sodium‐ion batteries.